Impact of foreign exchange rate movements on company profitability in the tobacco sector. A case study of the British American Tobacco Kenya limited - Darshna, Dinesh Kurji Patel (Strathmore University, 2020)
Any firm engaging in international trade is exposed to exchange rate risk, whether translation, transaction or economic risk. Knowing the impact or its extent can help t1rms evaluate potential positions they can take in the forex market to hedge their exposures. This study examines the impact of movements in exchange rates on profitability of firms in the tobacco industry in Kenya, specifically looking at a case of BAT Kenya. This study explores the impact on profitability by employing a V AR Model from the period of 1995 to 2018. Profitability is looked at in terms of three measures: Return on Equity (ROE), Return on Assets (ROA) and Return on Invested Capital (ROIC) and the main exchange rates incorporated in the study are the USD, Euro and the GBP. The main idea behind using a V AR Model was due to its characteristics of obtaining impulse responses which are highly beneficial for governments when formulating monetary policies that are also dependent on exchange rates. Findings of the study reveal statistical significance of the exchange rates, bit different for different exchange rates. Additionally, shocks in the exchange rates are highly likely to impact corporate profitability and therefore firms operating in internationai trade are likely to experience exchange rate exposure and therefore these results are highly beneficial for them. A major limitation ofthe study is the inadequacy of enough data points. Due to lhe dynamic macro environmeui: that the exehange rates are exposed to, there is yet a grcnt room for research considering the many major exchange rates that affect any finn's cash flows.
Submitted in partial fulfilment of the requirements for the Degree of Bachelors of Business Science in Finance at Strathmore University